Mutagenesis of PhaR, a Regulator Gene of Polyhydroxyalkanoate Biosynthesis of Xanthomonas oryzae pv. oryzae Caused Pleiotropic Phenotype Changes - Long, Ju-Ying; Song, Kang-Li; He, Xiang; Zhang, Bin; Cui, Xiao-Fang; Song, Cong-Feng (Frontiers in Microbiology, 2018)
Polyhydroxyalkanoates (PHAs) are intracellular carbon and energy storage materials produced in various microorganisms under nutrient-limited conditions. PhaR is a regulatory protein involved in PHA synthesis. Xanthomonas oryzae pv. oryzae (Xoo ) is one of the most important bacterial pathogens in rice and has PHA biosynthesis genes in its genome, but the biological function of phaR in Xoo is unknown. In this study, we investigated the effects of the mutagenesis of phaR gene in Xoo strain PXO99A. Compared to the wild type, the PhaR gene knock-out mutant PXO99phaR was hypermotile and showed decreased growth rates in both rich and limited nutrient media. PXO99phaR also showed almost 75% decrease in extracellular polysaccharide (EPS) production. When inoculated in rice leaves by leaf-clipping method, PXO99phaR displayed reduced virulence in terms of lesion length and bacterial multiplication compared with the wild type strain. PXO99phaR also showed enhanced hypersensitive response (HR) induction in the leaves of nonhost Nicotiana benthamiana with elevated hpa1 gene expression. Introduction of a cosmid containing the phaR coding sequence restored the phenotypes of the mutant to those of the wildtype strain. These results suggest that PhaR gene is an important gene that affects multiple bacterial characteristics, including EPS production, growth rate, defense response induced harpin production and motility, related to its virulence in plant.